Conversion economics for Alaska North Slope natural gas - Thomas, C.P.; Robertson, E.P. (Lockheed Idaho Technologies Company, 1995)
For the Prudhoe Bay field, this preliminary analysis provides an indication that major gas sales using a gas pipeline/LNG plant scenario, such as Trans Alaska Gas System, or a gas-to-liquids process with the cost parameters assumed, are essentially equivalent and would be viable and profitable to industry and beneficial to the state of Alaska and the federal government. The cases are compared for the Reference oil price case. The reserves would be 12.7 BBO for the base case without major gas sales, 12.3 BBO and 20 Tcf gas for the major gas sales case, and 14.3 BBO for the gas-to-liquids conversion cases. Use of different parameters will significantly alter these results; e.g., the low oil price case would result in the base case for Prudhoe Bay field becoming uneconomic in 2002 with the operating costs and investments as currently estimated.